Les porteurs de miroirs, de Platon à Robert Smithson - Olcèse, Rodolphe (Elephant & Castle, 2020)
This text aims to link the installations produced by Robert Smithson with the Yucatan mirror displacements (1-9) and Plato’s conception of pictorial mimesis in La République (livre X). This link makes it possible to show how Robert Smithson’s artwork revives Plato’s question of artistic mimesis and radically transformes it. Mimetic operations, and particularly those that can be produced by mirrors, do not lead to reproduce simply sensitives appearances, but to introduce differentiation into our relation to the reality. Robert Smithson’s Yucatan mirror displacements (1-9) gives a singular extension to the thesis defended by Saint John Damascene in the eighth century in the quarrel of images, which asserts that the image can express a dimension of invisibility.